Study on geopolymer mortar using hydrogen peroxide as foaming agent - Anuja, N.; Prabavathy, S. (Journal of Structural Engineering, 2024)
A new arising technology called geopolymer with zero percentage of cement has been developed in order to protect our environment from harmful CO₂ emission and further to save energy in the world for future use. Several drawbacks of ordinary portland cement such as low tensile strength, unstable crack propagation and low fracture resistance have been overcome by geopolymer. Further to make geopolymer as a good thermal insulating material with adequate strength, some foaming agents are added to the geopolymer mix. Foaming agents intend to develop pores inside the specimen to make it as lightweight. In this work, hydrogen peroxide is preferred as foaming agent which is added in diluted as well as undiluted form in the range of 0.3-1.8% at an interval of 0.3% so as to find the best specimen which has low density and thermal conductivity with adequate compressive strength. From the result, it was found that the geopolymer mortar cured at 80°C for 24 hours in hot air oven with 0.9% hydrogen peroxide in diluted form gives the best result with compressive strength and density of 4.641MPa and 1209kg/m³. It also gives low thermal conductivity of 0.141W/mK when compared to normal geopolymer mortar.